Spinal TB: Impact of Research Evidence on Clinical Practice - Jain, Anil K (Annals of the National Academy of Medical Sciences (India), 2018)
The evidence generated while treating the patients is the key for growth of science. Finding answers to series of research questions spread over many years may change the clinical practice. This presentation is based on 25 research questions, 44 publications while treating 3300 patients over last 28 years ( 1990-2017) which has substantially changed the objective of treatment in spinal tuberculosis (TB) from healing of lesion with sequelae of spinal deformity and paraplegia to achieving healed status with near normal spine.Three cases of late-onset paraplegia were evaluated (1990) by newly introduced MRI. The syringohydromyelia and severe cord atrophy were attributed as the cause of paraplegia. We conducted a series of prospective studies to define and correlate MRI observations on spinal cord in paraplegia and followed the treatment outcomes. The cord edema, myelomalacia, cord atrophy and syringomyelia were observed in cases with neural complications. The patients with cord edema and liquid compression are predictor for neural recovery, while dry lesions and myelomalacia for poor neural recovery. The mild cord atrophy was consistent with neural recovery while severe cord atrophy with sequalae of neural deficit. Upto 76% canal encroachment was found compatible with intact neural state. Spinal deformity in TB spine is better prevented than treated. The contagious vertebral body disease with intact disc spaces, subperiosteal and paravertebral, septate abscesses, intra-osseous and intraspinal abscesses are considered features of spinal TB and resolution of abscess and fatty replacement is characteristic of healing. The clinicoradiological predictors for diagnosing spinal TB in predestructive disease were defined. Only 35% patients achieved healed status on MRI by DOTS regimen at 8 months, Hence, it is unscientific to stop antitubercular treatment (ATT) at fixed time schedule. The criteria to suspect multi-drug resistant (MDR)-TB and guide to treatment were definedResidual Kyphotic deformity in spine TB produces severe proximal/distal degeneration of spine and/or late-onset paraplegia. We correlated the final kyphosis with initial vertebral body (VB) loss, where 1.5 VB height loss will produce 600 spinal deformity or more, hence surgical correction of spinal deformity is indicated. The surgical steps of kyphotic deformity correction are: anterior corpectomy, posterior column shortening, instrumented stabilization, anterior gap grafting and posterior fusion in a single stage and sequentially. The surgical incision of costo-transversectomy was modified so that kyphosis correction and posterior Hartshill instrumentation can be performed simultaneously. The retroperitoneal extrapleural approach for dorsolumbar spine was described. Meta-analysis of spinal instrumentation in TB spine established the lack of defined indication of instrumented stabilisation. Panvertebral/ long segment disease, kyphotic deformity correction are listed as indications of instrumented stabilisation in TB spine. The end point of treatment in spinal TB still eludes us to resolve the optimum duration of ATT regimen. The PET scan may be used to define it. We believe if a clinician works slow and steady on a series of research questions and by sustained focused efforts can change the clinical practice. We after this sustained research work could contribute in framing Bone and Joint TB guidelines and publish as monograph.
Keywords: Bone tuberculosis; TB spine; antitubercular therapy; kyphotic deformity